Redescriptions of Streblosoma bairdi (Malmgren, 1866) and Thelepus cincinnatus (Fabricius, 1780), based on types and material from type localities - de Matos Nogueira, João Miguel (Zootaxa, 2019)
Streblosoma bairdi (Malmgren, 1866) and Thelepus cincinnatus (Fabricius, 1780) are the type species of their respective genera, described from specimens from northern European waters, off Sweden and Greenland, respectively. Both species have subsequently been reported from many localities around the world, including some from much warmer waters. That is probably because the original species descriptions are very brief and do not include several characters currently considered important for the taxonomy of these genera. Several redescriptions have been provided for both species through the years, but the types were not examined and based on material far from their type localities. Both these species are herein redescribed, from type material or material from the type localities. It is recommended that all records of these species from locations far from their type locality should be carefully checked to confirm their identity.